Lung volume reduction with vapor ablation in the presence of incomplete fissures: 12-month results from the STEP-UP randomized controlled study - Gompelmann, Daniela; Eberhardt, Ralf; Schuhmann, Maren; Valipour, Arschang; Shah, Pallav; Herth, Felix; Kontogianni, Konstantina (Respiration, 2016)
Background: Emphysema patients with collateral ventilation (CV) will not benefit from valve therapy, the most common endoscopic lung volume reduction procedure. A recent randomized controlled trial (STEP-UP) of the alternative bronchoscopic thermal vapor ablation (BTVA) included patients with (CV+) and without interlobar CV (CV-). Objectives: This analysis evaluated the efficacy and safety of the CV+ population following BTVA. Method: A post hoc fissure analysis of the baseline computed tomography of all treatment and control patients was performed with the VIDA Diagnostics Apollo software. A patient was considered to be CV+ if either of the treated upper lobes was adjacent to a fissure that was <90% complete. The primary endpoints, forced expiratory volume in 1 s (FEV1) and St. George's Respiratory Questionnaire (SGRQ-C), were calculated for these CV+ patients following BTVA and safety results summarized. Results: 78% (35/45) of the patients in the treatment arm and 79% (19/24) of the patients in the control arm were found to be CV+. At 12 months, the FEV1 improvement of the treatment arm was 9.2%, as compared with a decrease of 5.4% in the control group, resulting in a mean between-group difference of 14.6% (p = 0.0137). The improvement in SGRQ-C of the treatment arm as compared to the control arm was 8.4 points (p = 0.0712). An increase in respiratory related serious adverse events was observed immediately following treatment, but most resolved with routine care. Conclusion: BTVA can achieve safe and clinically meaningful improvement in pulmonary function and quality of life in patients with CV. These randomized controlled trial subgroup results offer proof of a viable solution for CV+ patients.